The Implementation of Task-Based Teaching by Using Translation Method to Improve Student’s Reading Skill - Mahmud, Moh; Puteri Wahdani, Lailia Dyah (JELP Journal of English Language and Pedagogy, 2024)
Reading is one of the most important English skills for students to learn, This study aims to determine whether reading learning with translation learning can improve students' reading skills, gain students' perceptions and impressions of the task-based learning process, and to obtain increased student participation results in learning to read texts, This research method use Classroom Action Research Design, and this research consists of two cycles, The results of this study indicate that the application of the task-based teaching strategy with the translation method for class VII SMPN 2 Siliragung has a positive impact on students, especially in reading. This is evidenced by the average number of students who have increased in each cycle. In the preliminary study, the average number of students became 56, increased to 69.67 in the first cycle, and increased to 83 in the second cycle